The effect of shoulder muscle fatigue on active repositioning acuity and scapulothoracic resting alignment: A systematic review with meta-analysis. (July 2016) - Takasaki, Hiroshi; Lim, Edwin Choon Wyn; Soon, Benjamin
Abstract: Objectives: The purpose was to synthesize the current evidence for the impact of muscle fatigue on measures for active repositioning task of the glenohumeral or scapulothoracic movements including the absolute error and/or scapulothoracic resting alignment. Methods: We searched the PubMed, EMBASE, MEDLINE, CINAHL, SCOPUS, SportDiscuss and the Cochrane library databases. We included papers using a fatiguing task as part of their experimental design. Meta-analyses were undertaken for the active repositioning acuity of the glenohumeral outer/inner range of external rotation, glenohumeral inner range of internal rotation and scapulothoracic resting alignment in the scapular upward/downward rotation, anterior/posterior tilt and protraction/retraction planes. Qualitative data synthesis with standardized mean difference (SMD) was also conducted. Results: There was a significantly pooled SMD,  −2.10 (95% confidence interval −2.57 to −1.63), P  < 0.001) in active repositioning acuity of the glenohumeral outer range of external rotation before and after a fatiguing task. However, the pooled SMD in active repositioning acuity for other glenohumeral movements and scapulothoracic resting positions were not significant ( P  > 0.05). Conclusion: Shoulder muscle fatigue impairs active repositioning acuity of the glenohumeral outer range of external rotation. Conversely, the current evidence does not support such impairment for the remaining glenohumeral movements and scapulothoracic resting alignments.. Highlights: Muscle fatigue impairs proprioception in the outer range of external rotation. Proprioception in the inner range of rotation is not impaired by muscle fatigue. Scapulothoracic resting alignment is not affected by shoulder muscle fatigue. There is a lack of quality evidence in this research topic.